2002
DOI: 10.1016/s0920-5632(02)01416-0
|View full text |Cite
|
Sign up to set email alerts
|

Density matrix renormalisation group approach to the massive Schwinger model

Abstract: The massive Schwinger model is studied, using a density matrix renormalization group approach to the staggered lattice Hamiltonian version of the model. Lattice sizes up to 256 sites are calculated, and the estimates in the continuum limit are almost two orders of magnitude more accurate than previous calculations. Coleman's picture of 'half-asymptotic' particles at background field θ = π is confirmed. The predicted phase transition at finite fermion mass (m/g) is accurately located, and demonstrated to belong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 43 publications
6
40
0
Order By: Relevance
“…This is the first time that the second vector excitation has been found numerically. For the energy density and the two lowest mass excitations our results are consistent with the previous most precise simulations [2,3], with a similar or sometimes better accuracy. As shown in the supplementary material, we were also able to reconstruct the Einstein dispersion relation for small momenta ka ≪ 1.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This is the first time that the second vector excitation has been found numerically. For the energy density and the two lowest mass excitations our results are consistent with the previous most precise simulations [2,3], with a similar or sometimes better accuracy. As shown in the supplementary material, we were also able to reconstruct the Einstein dispersion relation for small momenta ka ≪ 1.…”
supporting
confidence: 91%
“…Similar to [2] our extrapolation error is then estimated by considering a third and fourth order polynomial through all six points, taking the error to be the maximal difference with the original inferred value.…”
Section: Special Features Of Gauge Invariant Mpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we determine the single-particle excitations for different values of α. Surprisingly, earlier numerical studies on the spectrum of the Schwinger model in the non-perturbative regime exclusively focussed on the cases α = 0 [19,23,62] and α = 1/2 [21][22][23]. An overview of the low-energy spectrum is for instance useful to have a better understanding of the dynamics induced by a quench in the form of an electric field.…”
Section: Introductionmentioning
confidence: 99%
“…One usually takes the bosonized version of these models which are local selfinteracting scalar theories, and can be investigated in an easier way [11,12]. The phase structure of the QED 2 with many flavors was mapped out from its bosonized version and it was shown that it exhibits only a single phase [13,14] as opposed to the single-flavor QED 2 (which is often referred to as the massive Schwinger model) [3-5, 11, 12], which possesses a symmetric strong coupling (e m e ) phase and the weak coupling (e m e ) phase with spontaneously broken reflection symmetry separated by the critical value (m e /e) c ∼ 0.31 as was shown by density matrix renormalization group (RG) technique [15,16] or by continuous RG method [14,17].…”
Section: Introductionmentioning
confidence: 99%